The Effect of Ineffective Monitoring, Change in Director, Financial Stability, and Good Corporate Governance on Financial Statement Fraud - Hayat, Hasbi Nur; Nengzih, Nengzih (Dinasti International Journal of Digital Business Management, 2025)
This study originated from the phenomenon of differences in interests between principals and agents.  Fraud occurs due to opportunities, justifications, and pressures, as indicated by the large number of financial statement manipulations that turn companies' losses into profits (window dressing). This study aims to analyze the influence of Ineffective Monitoring, Change in Directors, Financial Stability, and Good Corporate Governance on Financial Statement Fraud in State-Owned Enterprises listed in the period 2018-2023. The method used is a descriptive-verificative method with a quantitative approach, where data is obtained through the collection of secondary data in the form of company annual reports and analyzed using multiple linear regression with the help of the SPSS application. The research sample consists of 29 SOEs over 6 years of observation, resulting in a total of 174 panel data observations. The results of the study indicate that Ineffective Monitoring does not have a positive effect on Financial Statement Fraud. Change in Director has a positive effect on Financial Statement Fraud. Financial Stability does not have a negative effect on Financial Statement Fraud. Good Corporate Governance does not have a negative effect on Financial Statement Fraud. However, simultaneously, these four variables together have an effect on financial statement fraud